In Situ Photo Sonosynthesis of Organic/Inorganic Nanocomposites on Wool Fabric Introducing Multifunctional Properties. (15th December 2015) - Behzadnia, Amir; Montazer, Majid; Mahmoudi Rad, Mahnaz
Abstract: Here, a novel and efficient process is introduced for producing wool fabric with multifunctional features through facile in situ photosonochemical synthesis of organic/inorganic nanocomposites. The fabric was treated with titanium isopropoxide, silver nitrate and ammonia in a sonobath for 1 h at 75–80°C. The crystal phase of the sono‐treated samples was characterized by X‐ray diffraction. The uniform distribution of the nanocomposite on the fiber surface was proved by field emission scanning electron microscope, energy dispersive X‐ray and mapping patterns. Further, the composition of the nanocomposites was investigated by X‐ray photoelectron spectroscopy. The sono‐treated wool fabrics illustrated excellent photocatalytic activities toward discoloration of Methylene Blue under sunlight and UV‐A irradiation. Also the fabrics indicated reasonable antibacterial/antifungal activities against Staphylococcus aureus, Escherichia coli and Candida albicans . The tensile properties of the sono‐treated fabrics enhanced comparing to the untreated and even conventional stirrer‐treated fabrics. Moreover, a central composite design based on response surface methodology was used to study the influence of titanium isopropoxide and silver molar ratio on the prepared nanocomposites sonobath. Finally, the optimum molar ratio was reported for the best responses. Abstract : A novel efficient process is introduced for wool fabric with multifunctional features through facile in situ photo sonosynthesis of organic/inorganic nanocomposites. The fabric was treated with titanium isopropoxide, silver nitrate and ammonia in a sonobath at 75–80°C for 1 h. The uniform distribution of the nanocomposites on the fiber surface was proved by SEM, EDX and mapping. The sono‐treated wool fabrics illustrated excellent photocatalytic activities toward discoloration of Methylene Blue under sunlight. Also the fabrics indicated reasonable antibacterial/antifungal activities against S. aureus, E. coli and C. albicans . The tensile properties of the sono‐treated fabrics was also enhanced.